LINGUISTIC PORTRAIT OF THE 'SUPERFLUOUS PERSON': HOW MARKER WORDS (BOREDOM, MELANCHOLY, REFLECTION) FROM ONEGIN TO OBLOMOV AND WHAT THIS TELLS US ABOUT MODERN LITERATURE (International journal of artificial intelligence, 2026)
The article examines the linguistic analysis of the "superfluous man" type in 19th-century Russian literature and its transformation within modern artistic discourse. The author considers this phenomenon not only as a socio-psychological phenomenon but also as a special linguistic model of the individual, manifesting through a stable system of lexical-semantic and syntactic markers.